Bioremediation of sewage wastewater through microalgae (Chlorella minutissima) - SHARMA, GULSHAN KUMAR; KHAN, SHAKEEL A; SHRIVASTAVA, MANOJ; GUPTA, N; KUMAR, SANDEEP; MALAV, LAL CHAND; NOGIYA, MAHAVEER; DUBEY, S K (The Indian Journal of Agricultural Sciences, 2020)
Phycoremediation is a cost effective, environmentally sustainable, safe and alternative technology for remediation of wastewater. The present work was aimed to evaluate the role of inoculated microalgae (Chlorella minutissima) in phycoremediation of sewage wastewater. The selected microalgae removed 94.4% TDS, 88.9% of NO3 -N, 66.3% potassium, 67.4% phosphorus, 48.2% NH4 +, 93% (Biological Oxygen Demand) BOD5 and 80.5% (Chemical Oxygen Demand) COD. The wastewater obtained after phycoremediation have safe limit of nutrients to be used as irrigation water in agricultural fields. The results of this study suggested that growing algae in nutrient-rich sewage wastewater offers a new opportunity to bio-remediate pollution load of wastewater and use it for irrigation purposes.